Topological crystalline Kondo insulator in mixed valence ytterbium borides - Weng, Hongming; Zhao, Jianzhou; Wang, Zhijun; Fang, Zhong; Dai, Xi (Physical review letters, 2014)
The electronic structures of two mixed valence insulators YbB6 and YbB12 are studied by using the local density approximation supplemented with the Gutzwiller method and dynamic mean field theory. YbB6 is found to be a moderately correlated Z2 topological insulator, similar to SmB6 but having much larger bulk band gap. Notably, YbB12 is revealed to be in a new novel quantum state, strongly correlated topological crystalline Kondo insulator, which is characterized by its nonzero mirror Chern number. The surface calculations find an odd (three) and an even (four) number of Dirac cones for YbB6 and YbB12, respectively.